Efficacy of New Bioceramic Materials in Root Canal Obturation - Hasna Haridas; Mookambika Ramachandran; Drishya Kishore; Namitha Divakar; Aswanth Ajay; Sona Joseph (Journal of Pharmacy and Bioallied Sciences)
Background: The efficacy of root canal obturation is crucial for the long-term success of endodontic treatments. Recently, bioceramic materials have gained attention due to their superior biological and physical properties compared to traditional materials. Materials and Methods: In this study, 60 extracted human teeth with single canals were randomly divided into three groups (n = 20) based on the obturation material used: Group A (EndoSequence BC Sealer), Group B (BioRoot RCS), and Group C (Conventional Gutta-Percha with AH Plus Sealer). All canals were prepared using a standardized protocol and obturated using the respective materials. The quality of obturation was assessed using micro-CT analysis, measuring void volume percentage and adaptation to canal walls. Additionally, apical sealing ability was evaluated using a dye penetration test. Results: Group A showed a significantly lower void volume percentage (2.1% ±0.3) compared to Group B (3.4% ±0.5) and Group C (5.6% ±0.7) (P < 0.05). Micro-CT analysis revealed better adaptation to canal walls in Group A and Group B compared to Group C. The dye penetration test indicated that Group A had the least apical leakage (0.5 mm ± 0.2), followed by Group B (0.8 mm ± 0.3), and Group C (1.5 mm ± 0.4) (P < 0.05). Conclusion: The new bioceramic materials, EndoSequence BC Sealer and BioRoot RCS demonstrated superior performance in root canal obturation compared to the conventional AH Plus Sealer.